Rising food prices and falling grain stocks: short-run blips or new trends? - Pinstrup-Andersen, Per; Garrett, James L. (International Food Policy Research Institute, 1995)
Grain traders in 1995 may have wondered if they were about to relive the world food crisis of the early 1970s. Prices for wheat, rice, and maize shot up during the year, grain stocks continued a three-year fall, fertilizer prices increased, and food aid dropped to slightly more than half of what it was in 1992. Overall grain production declined only about 3.4 percent in 1995, following a 2.5 percent increase in 1994. And global stocks have been declining for a number of years. So why large price increases now? The authors explore the reasons for this phenomenon and try to shed light on whether it is a blip or a "trend". They examine the effects of rising prices on food security in low-income countries and what some countries have done to cope with price fluctuations that affect the international grain markets."